Bcl2 Family Functions as Signaling Target in Nicotine-/NNK-Induced Survival of Human Lung Cancer Cells. (20th May 2014) - Deng, Xingming
Abstract : Lung cancer is the leading cause of cancer death and has a strong etiological association with cigarette smoking. Nicotine and nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) are two major components in cigarette smoke that significantly contribute to the development of human lung cancer. Nicotine is able to stimulate survival of both normal human lung epithelial and lung cancer cells. In contrast to nicotine, NNK is a more potent carcinogen that not only induces single-strand DNA breaks and oxidative DNA damage but also stimulates survival and proliferation of normal lung epithelial and lung cancer cells. However, the molecular mechanism(s) by which nicotine and NNK promote cell survival, proliferation, and lung tumor development remains elusive. The fate of cells (i.e., survival or death) is largely decided by the Bcl2 family members. In the past several years, multiple signaling links between nicotine/NNK and Bcl2 family members have been identified that regulate survival and proliferation. This review provides a concise, systematic overview of the current understanding of the role of the pro- or antiapoptotic proteins in cigarette smoking, lung cancer development, and treatment resistance.